A new statistical approach to combining p-values using gamma distribution and its application to genome-wide association study - Chen, Zhongxue; Yang, William; Liu, Qingzhong; Yang, Jack Y; Li, Jing; Yang, Mary Qu (BMC bioinformatics, 2014)
Background Combining information from different studies is an important and useful practice in bioinformatics, including genome-wide association study, rare variant data analysis and other set-based analyses. Many statistical methods have been proposed to combine p-values from independent studies. However, it is known that there is no uniformly most powerful test under all conditions; therefore, finding a powerful test in specific situation is important and desirable. Results In this paper, we propose a new statistical approach to combining p-values based on gamma distribution, which uses the inverse of the p-value as the shape parameter in the gamma distribution. Conclusions Simulation study and real data application demonstrate that the proposed method has good performance under some situations.